2020
DOI: 10.5114/pjr.2020.95781
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous tumours detected during cancer patient staging: prevalence and patterns of occurrence in multidetector computed tomography

Abstract: The incidental detection of one or more additional primary tumours during computed tomography (CT) staging of a patient with known malignancy is rare but possible. This occurrence should be considered by the radiologist when a new lesion is detected, especially if the lesion location is atypical for metastases. The purpose of this report was to document the usefulness of total body CT scan to detect synchronous primary malignancies in cancer patients undergoing a staging workup. Material and methods: This was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…It is performed using a high-frequency linear transducer with the patient in the supine position. The examination allows the evaluation of the echostructure and the volume of the testes (normal value: 9-12.5 cc), the peri-testicular structures, and the proximal tract of the deferens [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Colour Doppler also allows the study of intra-testicular vascular flow and the study of reflux after Valsava test of the pampiniform plexus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is performed using a high-frequency linear transducer with the patient in the supine position. The examination allows the evaluation of the echostructure and the volume of the testes (normal value: 9-12.5 cc), the peri-testicular structures, and the proximal tract of the deferens [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Colour Doppler also allows the study of intra-testicular vascular flow and the study of reflux after Valsava test of the pampiniform plexus.…”
Section: Discussionmentioning
confidence: 99%
“…The imaging modalities routinely used to evaluate the reproductive system in males include ultrasound (US), magnetic resonance imaging (MRI), and interventional techniques such as venography and vesico-deferentography [ 10 , 11 ]. The scrotal ultrasound examination is the first level investigation [ 12 , 13 ]. It is performed using a high-frequency linear transducer with the patient in the supine position.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer, the 2nd most common tumor in patients over 65, is the most frequent primary tumor in sMPM patients [3]. Moreover, despite sMPM are rare entity, in the next decades, due to several considerations, their incidence will grow up.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Corvino et al reported a prevalence of sMPM of 3.6% and the most frequent first primary tumors were melanoma (17.8%), lymphoma (15.6%), and prostate carcinoma (15.6%). Moreover, among sMPM patients, the relative risk of other tumors increased with patient age and male sex [3]. Surgery, radiotherapy (RT) with/without chemo/hormonaltherapy are classically considered in the armamentarium of the cancer battle.…”
Section: Introductionmentioning
confidence: 99%
“…As regards the other complications, all of a non-specific nature, such as the occlusions on the bridle, the flies, and the strangulated laparoceles, CT played a fundamental role in assessing the site of the obstruction and the planning of the intervention based on the degree of urgency of the disease. In particular, CT indicates with extreme precision the location of the volvulus, the torsion of its mesenteric vascular axis, and with evidence, at times, of signs of both arterial and venous wall ischaemia as well as of faecaloid stasis within the loop concerned [28][29][30]. In the case of laparocele, the CT is definitive, especially in the presence of multiple laparoceles, in identifying the herniated loop and evaluating the state of its walls that may be affected by infarct phenomena in the event of constriction.…”
Section: Referencementioning
confidence: 99%